A pneumatic seeding machine. - Ahmad, Desa; Bakhtiar, Mohammad Reza; Othman, Jamarei; Ismail, Napsiah (2011)
The present invention related to a pneumatic seeding machine for planting seeds, the machine includes: (a) a chassis which is supported to move across and over fields by at least two wheels, wherein at least one of said wheels is drive wheel; (b) at least one unit planter with a seed hopper connected to said chassis; (c) a seed metering device provided at the at least one unit planter; wherein the seed metering device includes a seed plate having a plurality of circular array openings and tabs; an adjustable upper brush and a lower brush provided at a seed pick-up region within a seed chamber of the seed metering device to dislodge any extra or double seeds picked up by the seed plate; and a first separator and a second separator provided at a seed container of the seed metering device to direct seeds to the openings of the seed plate.